Analisis Proksimat dan Daya Terima Tortilla Chips Substitusi Tepung Biji Kelor sebagai Alternatif Camilan Sehat bagi Anak Sekolah Usia 6-12 Tahun - Elsa Mpeana; Nurdiana Nurdiana; Sri Rezeki (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Snacks consumed by school children are generally high in sugar, salt, and saturated fat, which may negatively affect health. One effort to improve nutritional intake is developing healthier snacks using local food sources, such as tortilla chips substituted with moringa seed flour (Moringa oleifera). This study aimed to analyze the proximate composition and acceptability of moringa seed flour–substituted tortilla chips as a healthy snack alternative for school children. The study employed an experimental design using a Completely Randomized Design with three formulations: F1 (45%), F2 (50%), and F3 (55%). The acceptability test results showed that F1 was the preferred formulation. The selected tortilla chips contained 13.228% protein, 35.415% fat, 20.311% carbohydrates, 4.283% moisture, and 1.4731% ash. Kruskal–Wallis analysis indicated no significant differences in organoleptic parameters among the formulations (p > 0.05). Therefore, tortilla chips with 45% moringa seed flour substitution demonstrated the highest acceptability and potential as a healthy snack for school children.